Under-Legislation in Electronic Trials and Renewing Criminal Law Enforcement in Indonesia (Comparison with United States) - Rian Saputra; Josef Purwadi Setiodjati; Jaco Barkhuizen (Journal of Indonesian Legal Studies, 2023)
This paper aims to propose the implementation of electronic justice within the Indonesian criminal justice system, focusing on the reform of criminal law enforcement. The research methodology employed is normative legal research. The findings of the study reveal two key points. Firstly, it is crucial to regulate digital-based criminal justice at the legislative level, particularly through the reform of the Code of Criminal Procedure (KUHAP). The current implementation of electronic criminal trials presents challenges, and the legal foundation for conducting such trials is established by external entities rather than the legislative institution. Therefore, incorporating regulations on electronic criminal trials in future KUHAP reforms is vital to facilitate criminal law reform. As it stands, electronic criminal trials lack specific legal regulations. Secondly, the existing KUHAP does not sufficiently address the issue of technological advancements, as it cannot anticipate rapid changes in technology. Consequently, a legal framework should be established to address this issue. This framework should ensure the availability of modern technological devices and necessary resources to facilitate digital-based criminal justice. Additionally, it should introduce laws governing electronic courts and initiate legal reforms through the revision of Law Number 8 of 1981 concerning Criminal Procedure Law (KUHAP). To provide an example, the United States has regulated electronic criminal proceedings through the Coronavirus Aid, Relief, and Economic Security Act (CARES Act), which implements fiscal stimulus policies and allows for video conferencing in certain cases. Such regulations can serve as a reference point for the implementation of electronic criminal proceedings in Indonesia.